name | natural-set |
version | 1.0 |
description | natural-set |
author | Joe Hurd <joe@gilith.com> |
license | HOLLight |
provenance | HOL Light theory extracted on 2011-02-19 |
show | Data.Bool |
⊦ ∀P. (∀n. (∀m. Number.Natural.< m n ⇒ P m) ⇒ P n) ⇒ ∀n. P n
⊦ ∀P. (∃n. P n) ⇔ ∃n. P n ∧ ∀m. Number.Natural.< m n ⇒ ¬P m
⊦ ∀P.
(∃x. P x) ∧ (∃M. ∀x. P x ⇒ Number.Natural.≤ x M) ⇔
∃m. P m ∧ ∀x. P x ⇒ Number.Natural.≤ x m
⊦ ∀P.
(∀m n. P m n ⇔ P n m) ∧ (∀m n. Number.Natural.≤ m n ⇒ P m n) ⇒
∀m n. P m n
⊦ ∀P.
(∀m. P m m) ∧ (∀m n. P m n ⇔ P n m) ∧
(∀m n. Number.Natural.< m n ⇒ P m n) ⇒ ∀m y. P m y
⊦ T
⊦ F ⇔ ∀p. p
⊦ ∀t. t ∨ ¬t
⊦ (¬) = λp. p ⇒ F
⊦ ∀t. (∀x. t) ⇔ t
⊦ ∀t. (λx. t x) = t
⊦ (∀) = λP. P = λx. T
⊦ ∀x. x = x ⇔ T
⊦ (⇒) = λp q. p ∧ q ⇔ p
⊦ ∀t. (t ⇔ T) ∨ (t ⇔ F)
⊦ (¬T ⇔ F) ∧ (¬F ⇔ T)
⊦ ∀m n. Number.Natural.≤ m n ∨ Number.Natural.≤ n m
⊦ (∧) = λp q. (λf. f p q) = λf. f T T
⊦ ∀P. ¬(∀x. P x) ⇔ ∃x. ¬P x
⊦ ∀P. ¬(∃x. P x) ⇔ ∀x. ¬P x
⊦ (∃) = λP. ∀q. (∀x. P x ⇒ q) ⇒ q
⊦ (∨) = λp q. ∀r. (p ⇒ r) ⇒ (q ⇒ r) ⇒ r
⊦ ∀m n. Number.Natural.< m n ∨ Number.Natural.< n m ∨ m = n
⊦ ∀P Q. P ∧ (∃x. Q x) ⇔ ∃x. P ∧ Q x
⊦ ∀P Q. P ∨ (∃x. Q x) ⇔ ∃x. P ∨ Q x
⊦ ∀P Q. (∃x. P x) ∧ Q ⇔ ∃x. P x ∧ Q
⊦ ∀P Q. (∃x. P x) ∨ Q ⇔ ∃x. P x ∨ Q
⊦ ∀P. (∀x. ∃y. P x y) ⇔ ∃y. ∀x. P x (y x)
⊦ ∀P.
P Number.Numeral.zero ∧ (∀n. P n ⇒ P (Number.Natural.suc n)) ⇒ ∀n. P n
⊦ (∀t. ¬¬t ⇔ t) ∧ (¬T ⇔ F) ∧ (¬F ⇔ T)
⊦ ∀P Q. (∀x. P x ∧ Q x) ⇔ (∀x. P x) ∧ ∀x. Q x
⊦ (∀m. Number.Natural.< m Number.Numeral.zero ⇔ F) ∧
∀m n.
Number.Natural.< m (Number.Natural.suc n) ⇔
m = n ∨ Number.Natural.< m n
⊦ (∀m. Number.Natural.≤ m Number.Numeral.zero ⇔ m = Number.Numeral.zero) ∧
∀m n.
Number.Natural.≤ m (Number.Natural.suc n) ⇔
m = Number.Natural.suc n ∨ Number.Natural.≤ m n
⊦ ∀t. ((T ⇔ t) ⇔ t) ∧ ((t ⇔ T) ⇔ t) ∧ ((F ⇔ t) ⇔ ¬t) ∧ ((t ⇔ F) ⇔ ¬t)
⊦ ∀t. (T ∧ t ⇔ t) ∧ (t ∧ T ⇔ t) ∧ (F ∧ t ⇔ F) ∧ (t ∧ F ⇔ F) ∧ (t ∧ t ⇔ t)
⊦ ∀t. (T ∨ t ⇔ T) ∧ (t ∨ T ⇔ T) ∧ (F ∨ t ⇔ t) ∧ (t ∨ F ⇔ t) ∧ (t ∨ t ⇔ t)
⊦ ∀t. (T ⇒ t ⇔ t) ∧ (t ⇒ T ⇔ T) ∧ (F ⇒ t ⇔ T) ∧ (t ⇒ t ⇔ T) ∧ (t ⇒ F ⇔ ¬t)
⊦ ∀p q r.
(p ∨ q ⇔ q ∨ p) ∧ ((p ∨ q) ∨ r ⇔ p ∨ q ∨ r) ∧ (p ∨ q ∨ r ⇔ q ∨ p ∨ r) ∧
(p ∨ p ⇔ p) ∧ (p ∨ p ∨ q ⇔ p ∨ q)